2016
DOI: 10.1007/s10549-016-4064-9
|View full text |Cite
|
Sign up to set email alerts
|

Weekly paclitaxel plus carboplatin with or without trastuzumab as neoadjuvant chemotherapy for HER2-positive breast cancer: loss of HER2 amplification and its impact on response and prognosis

Abstract: Our study has provided new evidence that anti-HER2 treatment has a significant impact on HER2 loss. Far more importantly, the loss of HER2 amplification could identify non-pCR patients with high risk of disease relapse, which might help in tailoring following systemic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 28 publications
3
46
0
Order By: Relevance
“…To date, phase II and III trials have not been conducted to explore trastuzumab use following trastuzumab plus NAC administration preoperatively in cases who did not achieve pCR. The efficacy of anti-HER2 agents in non-pCR responders also remained controversial [42]. The present study results revealed that these patients gained benefits from using trastuzumab maintenance, although they are less likely to respond to trastuzumab plus NAC.…”
Section: Biomed Research Internationalmentioning
confidence: 60%
“…To date, phase II and III trials have not been conducted to explore trastuzumab use following trastuzumab plus NAC administration preoperatively in cases who did not achieve pCR. The efficacy of anti-HER2 agents in non-pCR responders also remained controversial [42]. The present study results revealed that these patients gained benefits from using trastuzumab maintenance, although they are less likely to respond to trastuzumab plus NAC.…”
Section: Biomed Research Internationalmentioning
confidence: 60%
“…Secondly, the number of HER2 negative tumor cells may increase after trastuzumab-based chemotherapy. Recent studies in breast cancer patients have indicated that trastuzumab-based chemotherapy has a significant impact on loss of HER2 positivity, and have suggested that treatment-induced clonal selection, biological modification, and tumor heterogeneity could explain this impact (25,26). HER2-positive gastric tumor cells have been shown to have higher chemosensitivity compared with HER2-negative gastric tumor cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of neoadjuvant chemotherapy (NAC), some studies indicate insufficient concordance rates for HER2 between pre-NAC CNB and post-NAC surgical specimens, which indicates that HER2 should be re-tested after NAC [ 18 , 19 ]. The loss of HER2 positivity in the surgical specimen after NAC is associated with poor recurrence-free or disease-free survival and could potentially indicate the need for further systemic therapy [ 18 , 20 , 21 ]. Data on the conversion of biomarkers such as HER2 among Swedish breast cancer patients are largely lacking but an evaluation is highly relevant since laboratory methods can vary between countries and routines for re-testing differ.…”
Section: Introductionmentioning
confidence: 99%